91 Great ormond street hospital SUMMER SCHOOL 2020 – embracing the #digitallife in conferencing. (30th November 2020) - Tutt, Abbie; Liu, Shuang; Smith, Jonathan; Poisson, Justin; Blackburn, Simon; Willock, Marissa; Poisson, Jeroen; Palmer, Nicola; Brown, Shereen; Wheeler, Olivia; Stow, Peter; McGonegal, Ellie; et al.
Abstract : Background: Social Media is an accompanying staple to conferences but also allows attendees who are attending virtually to interact with the day. GOSH Summer School (GSS) is normally run as a face to face event but had to be moved to a virtual set up this year due to the impact of Covid-19. This forced our attendees to change the way they networked and interacted with the day and how we dispersed education to the attendees. Methods: Two main accounts were used to document the day; Twitter: @GOSHPGME and Instagram: @pgme.education. Positive feedback, attendees 'set ups' and screenshots (in replace of taking photos) of the talks were shared. Attendees were encouraged to use the hashtag #GoshSummerSchool or send photos to GOSH PGME Instagram. Results: The PGME Twitter account gained 155 followers and was mentioned 196 times. This resulted in 2351 profile visits to the account and overall, 56.1K impressions were made throughout GSS. On Instagram, 24 posts were made and gained 77 new followers. There was an average of 30.5 likes, 0.5 comments, 3.9 post sends, 5.9 post saves, 26.6 profile visits and 436 views per post. 50 posts per day were added to the story feature of Instagram mainly featuring attendee set ups and opinions of the talks given. During the GSS, a survey about which additional resources students use to gain knowledge in medicine, social medial received 48% votes. Discussion: The engagement statistics and broad use of social media to compliment the GSS shows how it can be used to increase engagement on virtual conferences. The uptake of social media interaction shows the potential of the platform to enable increased engagement and sharing of medical education. This also enables the increase of long-distance attendees allowing GOSH to open medical education beyond London schools and even worldwide.